Epidemiology and types of oral cancer - Al-Sharif, Rajeh M.; Batwa, Dalia Y.; Alotaibi, Turki N.; Alwadai, Naif M.; Alsharif, Abdullah H.; Azhar, Nedaa A.; Moulana, Arjumand A.; Alahmadi, Shoroug M.; Althobaiti, Meshal Y.; Bayyumi, Duaa F.; Alzahrani, Wejdan I. (International Journal Of Community Medicine And Public Health, 2022)
Oral cancer is a subset of head and neck cancer and usually refers to different neoplastic conditions that impact any tissue within the oral cavity. Evidence shows that these malignancies are associated with different complications over the affected patients. The present literature review will discuss the epidemiology and types of oral cancer based on evidence from relevant studies within the literature. Estimates show that oral cancer is a common condition with high prevalence rates globally. However, we have identified several factors across the different relevant investigations, including smoking, alcohol intake, age, socioeconomic status, immunocompromised state, and genetics. This might explain the inconsistent findings regarding the prevalence and mortality rates of the conditions among worldwide studies. Moreover, squamous cells carcinoma is the commonest type of oral cancer. However, other types might also be identified as adenocarcinoma, sarcoma, melanoma, and lymphoma. These lesions can also be found at different places within the mouth cavity, including lips, tongue, and salivary glands. Therefore, healthcare authorities should plan adequate interventional strategies targeting the risk factors to properly control the disease and reduce its burden.